PENINGKATAN DAN PEMBUATAN VIDEO PRODUK SPEEDUINO STANDALONE ECU ATHENA GARAGE JOGJA - Ibnu Hadi Purwanto; Jeki Kuswanto; Dhimas Adi Satria (Jurnal Abdi Insani, 2023)
Digital marketing is a feature of social media that can connect digital technology which combines with traditional communication to achieve marketing goals. Delivering products in the form of videos or processed photos can be a method for product marketing development. Using the right marketing application can also boost promotions. This community service program aims to document the manufacture of the speeduino and find out how the implementation process went into the machine. Speeduino is an open source machine management system. The method used in this service involves analysis and observation of partners to find out the problems faced by partners in the development of making Speeduini products. Another method used is practice and direct observation of objects to find out their functions and features in more depth. Through the video capture technique applied, it is hoped that it will be able to present to users how to configure and optimize the potential of the Athena Garage speeduino. The result of this community service program is increased knowledge in speed production and video making for promotional media at the Athena Garage workshop. This program not only produces tools, but also produces videos that can be used as guidance and education for beginners in installing and using Speeduino products from Athena Garage Jogja. The conclusion of this activity is, by applying audio visual techniques combined with Arduino technology in Speeduino products, you can optimize both product performance and product marketing. The implication of this community service program is the development of Athena Garage in innovation in the world of automotive and information technology.